ANALISIS BIAYA MATERIAL PEKERJAAN DINDING MENGGUNAKAN BETON PRECAST DAN BATA RINGAN PADA PROYEK GEDUNG PT. MATTEL INDONESIA CIKARANG BEKASI - Raafidiani, Reni; Garata, Garwin; Febriansya, Aditia (Jurnal TEDC, 2024)
PT. Mattel Indonesia in Cikarang Bekasi during structural work so the contractor must determine the strategy that must be used to speed up the completion of the project. Replacing the materials used in wall work is one alternative that can be done by the contractor. Where the yield value is there are two material choices, namely precast concrete with a yield of 246,131.11 m2 and a lightweight brick yield of 232,101.6 m2. Thechoice of the two materials is determined by considering a study of the material costs required to install each material. The analysis carried out begins by studying the literature on the management of each material and knowing the conditions in the field. The design budget (RAB) required for precast concrete walls and lightweight brick walls is comparable. The duration required for the work of making precast concrete walls and lightweight brick walls is comparable. In terms of material cost comparison, precast concrete walls have the most effective SOP to apply in this project. Of all the variables compared, the material that is suitable to replace wall material in this project is precast concrete walls.